2014
DOI: 10.1179/2151090314y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the usefulness of Kinesiograph as an aid in the diagnosis of TMD: a review of Manfrediniet al.'sstudies

Abstract: The publications by Manfredini et al. recognized proponents of the psychosocial model of TMD, including the 2013 article, appear to be part of a campaign denying an occlusion: TMD relationship and disparaging the specific computerized measurement devices and the dentists using them in the management of their TMD patients using neuromuscular occlusion dental treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…On the other hand, Manfredini et al found no significant differences between sEMG derivations of TMD patients and controls in their studies and questioned at the same time the validity of kinesiographs, which should be used as an alternative [ 31 ]. However, with regard to kinesiographs, Cooper [ 32 ] provided conclusive refutations of these findings. In contrast to sEMG derivations, ultrasound axiographies are found to be almost invariably positive, valid, sensitive, and beneficial for use in TMD therapy in the relatively small body of literature [ 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Manfredini et al found no significant differences between sEMG derivations of TMD patients and controls in their studies and questioned at the same time the validity of kinesiographs, which should be used as an alternative [ 31 ]. However, with regard to kinesiographs, Cooper [ 32 ] provided conclusive refutations of these findings. In contrast to sEMG derivations, ultrasound axiographies are found to be almost invariably positive, valid, sensitive, and beneficial for use in TMD therapy in the relatively small body of literature [ 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used device to evaluate MM is the mandibular kinesiograph, which also contains a facebow and has been criticized for inconsistent results. 29 The earlier techniques analyzed only the symmetry of the superior contact border movements. In the present study, the symmetry of Posselt polygons was evaluated, and therefore, superior and opening border movements were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…There is little doubt that these electronic tracking appliances are accurate. However, the controversy is how tracking findings should be interpreted in terms of best patient management and therapy (22,23). Contentious assumptions in particular are the claims that (i) the trajectories of the mandible or the condyles may be examined in detail and therefore provide an improvement for decision of appropriate therapy.…”
Section: Computer-assisted Patient Diagnosticsmentioning
confidence: 99%
“…Several software products have come and disappeared again over the years (remember Moore's law), but multiple sophisticated products remain. The American Dental Association lists 30 commercial products on their website (36), but there are numerous more, amongst these, for example Bite FX, 23 Consult PRO Suite, 24 CurveED, 25 Dental Explorer 3D, 26 Dental Master, 27 Dental Patient Information, 28 Dental Patient Education Software 29 and Orasphere Patient Education system. 30 An even more advanced form of computer-assisted communication software enables a graphic representation of the intended treatment outcome as a basis for patient-provider deliberations.…”
Section: Computer-assisted Communicationmentioning
confidence: 99%
See 1 more Smart Citation